Safety of Atrovent® CFC-free inhaler: respiratory events reported from an observational cohort study in England. (9th October 2017) - Osborne, Vicki; Layton, Deborah; Fogg, Carole; Tong, Edward; Shakir, Saad A W
Abstract: Objectives: The aim of the study was to identify any unexpected clinical events associated with starting the new CFC-free formulation of Atrovent® MDI in general practice in England. Methods: An active surveillance cohort study was conducted with a focus on selected clinical events, including respiratory symptoms, in past users of Atrovent® CFC MDI ('switchers') and Atrovent® naïve users. Incidence density rate ratios (with 99% confidence intervals) for events occurring in the first 3 months of exposure (risk period-ID1-3 ) compared to 3 months prior to starting treatment (reference period-IDR ) were calculated. Results: The cohort consisted of 13 211 patients (median age 70 years, 50.1% female; 63.5% prior users of Atrovent® CFC MDI ('switchers')). Common respiratory events occurred at higher rates after starting treatment than before for switchers, for example lower respiratory tract infection (LRTI) [ID1 /IDR = 1.45 (99% CI: 1.17, 1.81)] and worsening asthma [ID1 /IDR = 1.58 (99% CI: 1.00, 2.51)]. Of these events only LRTI was significant for Atrovent® naïve patients [ID1 /IDR = 1.42 (99% CI: 1.04, 1.95)]. Conclusions: The results of this study suggest effect modification of risk as a result of prior Atrovent® CFC MDI use. Overall, Atrovent® CFC-free MDI appeared to be reasonably well tolerated in the immediate postmarketing period and the safety profile appeared similar to that of the CFC formulation.